Motivação para aprender música sob a perspectiva da teoria da autodeterminação: um estudo com alunos da rede pública do Município de Mossoró - Menezes, Danilo Augusto de (2021)
This study aimed to investigate the motivational quality of public school students in elementary and high school in musical activities from the perspective of the Self-Determination Theory. The theoretical framework used was based on the theory of self-determination, which analyzes the reasons why individuals engage in or avoid certain activities. This macro-theory states that all people have a natural aptitude for self-regulation, for this reason it defends the concept of internalization, evidenced through a continuum of self-determination presented in the mini-theory of organismic integration. The research presents a quantitative approach, descriptive, exploratory and correlational. To this end, a specific instrument of measurement was created, the Motivational Scale of Basic Education Music Students (EMEMEB), applied via the internet to a sample of 726 public school students in institutions established in the city of Mossoró-RN. The data obtained from the sample were analyzed using descriptive and inferential statistics, using some statistical procedures: frequencies, means, standard deviation, factor analysis, internal consistency analysis using Cronbach Alpha, analysis of variance using Anova and Kruskal Wallis and Pearson Correlation analysis. The results of this study revealed that the motivation of music students tends to be higher for autonomous motivation, obtaining the highest means in intrinsic motivation. Regarding the context variables, we concluded that for this sample, men and women with different age groups have the same motivational quality. However, we noticed that students from the municipal network showed significant values of controlled motivation, surpassing the values from the state network. Comparing motivation between different classes, it was found that autonomous motivation remained constant, while controlled motivation among students from 6st to 3st year of high school showed a decrease in the transition from elementary school II to high school